APOCRINE CARCINOMA OF BREAST: A RARE CASE REPORT - BB, SHINDE; ANMOL J, CHANDAK; DD, GIRIJI; SATISH R, SONWANE (International Journal of Clinical and Biomedical Research, 2015)
Apocrine carcinoma of breast is a very rare form of breast malignancy represent about 0.4% of all invasive ductal carcinoma (IDC). Though clinical presentation and gross appearance are indistinguishable from classic IDC, they have distinct cytological, histopathlogical and immunohistochemical features. Tumor cells are characterized by typical apocrine features large cells with abundant eosinophilic granular cytoplasm and large pleomorphic vesicular nuclei and prominent nucleoli. It tends to show estrogen, progesterone receptors and her2/neu negativity and show positivity for Gross Cystic Disease Protein Fluid -15 (GCDPF-15). We report a case of 65 year old female presenting clinically as lump in right breast in upper inner quadrant since four months and having similar cytological, histopathological and immunohistochemical features. KEYWORDS: Apocrine carcinoma; Breast malignancy; Immunohistochemistry.